Integrating Venom Peptide Libraries Into a Phylogenetic and Broader Biological Framework - Chase, Kevin; Watkins, Maren; Safavi-Hemami, Helena; Olivera, Baldomero M. (Frontiers in Molecular Biosciences, 2022)
The venomous marine snails are conventionally divided into three groups, the cone snails (family Conidae), the auger snails (family Terebridae) and the turrids (formerly all assigned to a single family, Turridae). In this study, a library of venom peptides from species conventionally assigned to the genus Turris was correlated to a phylogenetic analysis. Nucleotide sequences of multiple genes from transcriptomes were used to assess the phylogenic relationships across a diverse set of species. The resulting tree shows that as conventionally defined, the Conoidean genus Turris, is polyphyletic. We describe a new genus, Purpuraturris gen. nov., that comprises the outlier species. In addition to morphological distinctions, molecular data reveal that this group are more closely related to Unedogemmula and Turridrupa than to Turris sensu stricto. The correlation between phylogenetic information and multiple peptide sequences from the library of venom peptides was used to highlight those peptides mostly likely to be unique and intimately associated with biological diversity. The plethora of peptide sequences available requires two prioritization decisions: which subset of peptides to initially characterize, and after these are characterized, which to comprehensively investigate for potential biomedical applications such as drug developments.